THE RELEVANT OF PSYCHOLOGICAL CAPITAL ON ADAPTIVE PERFORMANCE BEHAVIOR AMONG YOUNG PROFESSIONALS: A CONCEPTUAL STUDY IN MALAYSIA CONTEXT - Ummi Kalsum Binti Hassian; Rachel Samuel A/P Samuel (International Journal of Accounting, Finance and Business, 2021)
Adaptive Performance Behaviour, the focus of this study, has receive much attentionas new workplace demands require flexible employees who are tolerant of uncertainties andcan successfully perform in dynamic, competitive environments. This study examines therelevance of psychological capital on adaptive performance behaviour in the context of youngprofessionals in the Malaysian service sector. Adaptive performance behaviour is highlyrelevant in firms where the business models and management are volatile due to technologicalor market evolution and environmental changes. In addition, the study also examines howpsychological capital can enhance adaptive performance behaviour. Data will be collectedfrom 103 young professionals in the Malaysian service sectors via survey questionnaireadopted from related literature and interviews from practitioners. Purposive sampling is atechnique which involves the researcher choosing sampling units based on existing, scientificknowledge or the researcher’s professional judgement. The sampling frame of this studyincludes all young professionals within the service sectors listed in the Federation ofManufacturing Malaysia Industry (FMM) directory 50th edition. The data collected will beanalysed using structural equation modelling via Smart PLS. Self Determination Theory is usedas the underpinning theory for this study as this theory offers a well-supportedconceptualization which proposes that motivation is best represented by conceptually distinct,yet complementary, types of behavioral regulations experienced by individuals to varyingdegrees.